Needle-Knife Fistulotomy for the Rescue: An Unusual Cause of Iatrogenic Extrahepatic Biliary Obstruction. (30th January 2018) - Ulmer, Laura L.; Jha, Lokesh K.; Bhogal, Neil; Kapur, Saurabh; Chandan, Saurabh; Eichele, Derrick; Bhat, Ishfaq; Singh, Shailender
Abstract : A 71-year-old male presented to our institution with cholestatic hepatitis after having recently undergone upper endoscopy for treatment of gastrointestinal bleeding. Further investigation with endoscopic retrograde cholangiopancreatography revealed a hemostatic clip on the ampulla of Vater. After initial attempts at cannulation of the common bile duct were unsuccessful, biliary decompression was achieved by use of needle-knife fistulotomy. A common bile duct stent was placed and the liver function tests improved prior to discharge.